9B.08: CARDIAC AND VASCULAR DAMAGE IN PATIENTS WITH PRIMARY ALDOSTERONISM AND ESSENTIAL HYPERTENSION. (June 2015) - Bertacchini, F.; Paini, A.; Salvetti, M.; Casella, E.; Rosei, C. Agabiti; Colonetti, E.; Donini, C.; Maruelli, G.; Rizzoni, D.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: Primary aldosteronism is a relatively common condition in hypertensive patients. Only few studies, in small groups of patients, have evaluated large arteries alterations. In some, but not in all studies, positive relationship with vascular damage was observed. Aim of the study: To compare the prevalence of cardiac and large arteries vascular organ damage in patients with essential hypertension (EH) or primary aldosteronism (PA). Design and method: In 243 consecutive patients with no interfering therapy (147 M, mean age 48 ± 11 years) a routine blood sample, including measurement of aldosterone/renin ratio (ARR) and saline load if ARR>30, was obtained. Echocardiography, carotid ultrasound and measurement of pulse wave velocity (PWV) were performed. We considered 3 groups: 48 patients with EH (ARR < 30); 122 patients with positive ARR screening but negative saline load (indeterminate aldosteronism, IA); 73 patients with PA (positive ARR and post saline aldosterone >100ng/ml)(51 % with adrenal adenoma). Results: No differences between groups were observed in age, gender, BMI, BP values (clinic and 24 hours), glucose, lipids and renal function. LVMI was greater in PA vs both IA and EH (PA 45 ± 18, IA 39 ± 12, EH 39 ± 10 gr/m2.7, p < 0, 05). Left atrial volume/BSA was significantly greater in PA vs EH (PA 27 ± 10, IA 24 ± 8, EH 23 ± 6 ml/m2, p < 0, 05 for PA vs EH). A positive correlation was observed between ARR and LVMI (r = 0, 20 p = 0, 002), left atrium volume (r = 0, 201, p < 0, 001) and relative wall thickness (r = 0, 394, p < 0, 005). Indices of vascular damage did not differ between groups (see table). Aldosterone levels and ARR were not significantly correlated with indices of vascular damage. Figure. No caption available. Conclusions: A greater prevalence of cardiac, but not of large arteries damage is observed in PA as compared to EH when a simultaneous assessment of cardiac and vascular OD is performed.